Penyelesaian Sengketa Penggelapan Hasil Kebun di Atas Tanah Landerform - Ida Bagus Made Murda Soma Widya; I Made Sepud; I Ketut Sukadana (Warmadewa Press, 2021)
Embezzlement is an act that is detrimental to the country's economy. Embezzlement activities are carried out on the assumption that making money is faster than having to work by following the rules of the company. Community behavior reflects low moral values. This study aims to analyze the arrangement of and describe the procedures for settling disputes over embezzlement of Landreform land crops. This research uses normative legal research with a statutory approach that is based on law as the basis for research. The data used are sourced from primary and secondary legal materials. The research results show that the applicable law is not so important for some people who have power over a building or land ownership and prefer power over land that should not be private property. As for the regulation of Landreform is a prohibition aimed at all people who want to control land beyond their ability or part of it without permission and notify their intentions in advance to others. Settlement of disputes over embezzlement of land reform land products can be resolved by non-litigation (outside the court) and litigation (in court).